Pengaruh Praktik Human Capital Terhadap Kesejahteraan Petani Garam Melalui Pengembangan Keterampilan di Desa Muarabaru - Fahrullah, Fahrullah; Setyaningrum, Retno Purwani; Dasman, Sunita (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2024)
The study aims to find out the impact of human capital practice on the welfare of salt farmers by considering skill development mediation. Effective human resources management practices include training, skill development, and empowering farmers to improve productivity and product quality. The research method used is quantitative, with a survey approach. The data was collected through a questionnaire that was distributed to 70 randomly selected salt farmers. The independent variable in this research is human resource management practice, which includes training, skill development, and business management. The dependent variable is the welfare of salt farmers, measured through improved income, quality of life, and market access. The collected data will be analyzed using the statistical approach and model system SEM PLS version 23. Research results show that human capital practices have a significant impact on the well-being of salt farmers, mediated by skill development. Skill development specifically has a major contribution to increasing productivity and farmers' incomes. This study concludes that investing in manicure resource management practices and skill development is an effective strategy to improve the welfare of salt farmers in the village of Muarabaru.